IMMUNE CORRELATES OF ACUTE MYCOBACTERIUM TUBERCULOSIS INFECTION IN HOUSEHOLD CONTACTS IN KAMPALA, UGANDA - WHALEN, CHRISTOPHER C. (2006)
To determine immunologic and epidemiologic correlates of acute Mycobacterium tuberculosis infection in household contacts of infectious tuberculosis cases, we performed a prospective, community-based cohort study of index cases and their household contacts in Kampala, Uganda. Contacts were evaluated for tuberculin skin test (TST) conversion over two years. Interferon-γ expression was measured using a whole blood assay after stimulating with M. tuberculosis culture-filtrate. In 222 contacts with a TST less than 5 mm at baseline, the one-year rate of TST conversion was 27%. The TST conversion was associated with the infectiousness of the index case and proximity of contact. Interferon-γ levels at baseline were greater among TST converters compared with those who did not convert. The risk of TST conversion increased four-fold as the baseline interferon-γ increased 10-fold, but only in contacts with BCG vaccination. In household contacts of tuberculosis, interferon-γ responses to non-specific mycobacterial antigens may be used to make an early diagnosis of tuberculosis infection, especially in resource-limited settings where bacille Calmette-Guérin vaccination is commonly used.